THE USAGE OF STUDENT’S ACTIVITY SHEET TO IMPROVE THE MATHEMATICS LEARNING OUTCOMES FOR 8TH GRADE - Endah Anis Sriyekti; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
The teacher uses of the worksheet in a studying process are rare, but actually, the case is students may active through do worksheet during the studying process, which is by the low math test scores of students are the background of the research. The research aims to improve the mathematics student’s outcomes grade VIII Muhammadiyah Junior High School 2 Godean (SMP Muhammadiyah Godean 2) in an odd semester in the academic year 2016/2017 through using of student’s worksheet (LKS). This research is Classroom Action Research (CAR), implemented in the 8th grade in SMP Muhammadiyah 2 Godean in the academic year 2016/2017 on August 16, 2016, through to September 6, 2016. The subject of this research is the students of class VIII C, which consists of 32 students. Action performed in two cycles. Each cycle consists of planning, implementation, observation, and reflection. At the same time, the object of this research is the use of student’s worksheets. The data will be collected using observation and tests. The analysis data are used descriptive qualitative analysis. The result of the research showed that using a student’s worksheet on the mathematics studying process could increase the student’s outcomes in every cycle. The first cycle average of the student’s outcomes of the end cycle test was 58,33 with the individual completeness on the first cycle was 25%. Whereas the average of the second student’s outcomes end cycle test was 65,56 with the individual completeness on the second cycle was 34,37%.